COMPANY MANAGEMENT ORGANIZATIONAL COMMUNICATION TO FORM STAFF HR INNOVATION IN TIDAL SWAMP LAND MANAGEMENT - Rico Rico; Risa Dwi Ayuni; Muzahid Akbar Hayat; Dewi Merdayanty; Siti Fatimah (Jurnal Ekonomi, 2022)
This study aims to determine the communication of the company's management organization to form staff innovations in managing tidal swamp land to become potential plantations. This research uses descriptive qualitative method. In dealing with the management of the Tidal Swamp area as a plantation area, a company must have good organizational communication within the scope of management to improve the innovations of human resources for plantation staff who are reliable and able to carry out the mandate properly so that the company's vision and mission can be achieved as expected. The strategy carried out by the Company's management with symbols or forms of organizational communication that they organize in an istiqomah culture of carrying out the mandate has succeeded in changing plantation governance for the better and has potential on marginal land.